Faktor-Faktor yang Mempengaruhi Praktik Pertama Kali Melakukan Hubungan Seksual pada Remaja Putri di Sumatera Utara - Vina Estetika Pakpahan; Sri Winarni; Dharminto Dharminto; Cahya Tri Purnami (Jurnal Manajemen Kesehatan Indonesia, 2023)
Based on a survey by the Central Bureau of Statistics in 2012, 48 out of 1,000 pregnancies occurred in adolescents aged 15-19 years. The occurrence of pregnancy at a young age & sexually transmitted diseases are the impact of having sex before marriage in adolescents. This study aims to determine the relationship between several factors with the practice of having sex for the first time and the age at first having sexual intercourse in young women in North Sumatra. The type of research used is explanatory research with a cross sectional study design. Research sampling is based on the research population, which means that all populations are samples. The sample obtained is 643 young women aged 15-24 years. The data used in this study is secondary data from the 2017 IDHS. This study found that the majority of young women aged 15-24 years in North Sumatra had never had sex, and for young women who had had sexual intercourse, it was found more in the age group ≤20 years than in the > 20 year age group. Factors that are not related to the practice of having sexual relations with young women for the first time in North Sumatra are education level (p-value = 0.089), economic status (p-value = 0.096), employment status (p-value = 0.138), and number of accesses. mass media (p-value = 0.102) and the intensity of mass media (p-value = 0.091). Factors related to the age of first sexual intercourse among young women in North Sumatra were education level (p-value=0.000) and economic status (p-value=0.007). The conclusion of this study is that most of the young women aged 15-24 years in North Sumatra have never had sex, but for the young women who have had sexual intercourse, it is found more in the age group ≤ 20 years.